DIFFICULTIES IN LEARNING GERMAN NOUN GENDER: A METHODOLOGICAL AND PSYCHOLINGUISTIC APPROACH - Kovser Abbasova (Foundations and Trends in Research, 2025)
This paper explores the difficulties encountered in determining the grammatical gender of nouns in the German language, with a specific focus on Azerbaijani learners. German, as a highly inflected language, assigns each noun to one of three genders: masculine, feminine, or neuter. The absence of a grammatical gender system in Azerbaijani creates additional challenges for learners, leading to frequent errors in article usage, adjective agreement, and pronoun selection. The study identifies the main linguistic, cognitive, and methodological factors contributing to these difficulties. It further analyzes how morphological patterns, semantic associations, and historical irregularities in German influence the learner’s ability to internalize gender rules. To address these challenges, the paper proposes several teaching strategies, including systematic pattern recognition, mnemonic devices, visual aids, and contextual immersion. The findings suggest that a multi-dimensional approach combining linguistic explanation and practical exposure significantly improves learners’ mastery of gender usage in German